Sepak Bola sebagai Media Dakwah Islam dan Peredam Islamophobia di Inggris - Johan Septian Putra; Egi Gianturi; Adetia Andri (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2024)
Islamophobia is a phenomenon that occurs in the world, especially among people who live in the western part of the world. With his fame and support from football fans, Moh. Salah is not afraid to show his identity as a Muslim footballer. This article examines the role of the media and the existence of Moh. It is wrong to reduce anti-Islam sentiment among European society, especially in the UK. The research in this article follows qualitative methods so it is in the qualitative descriptive category because it collects data and information about the research object. The findings in the article are that mass media and social media provide positive reporting regarding Moh's identity. Salah as a Muslim footballer has an influence on differentiating the public's perception of anti-Islam to pro-Islam, thereby reducing the phenomenon of Islamophobia in British society.